IMPLEMENTASI MODEL FLIPPED CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR - Ramly, Rizal Arizaldy; Ariaty, Eka; Ariandini, Nur (Universitas Muhammadiyah Makassar, 2025)
This research departs from the importance of student learning outcomes, but in reality these learningoutcomes are still relatively low. To overcome this problem, a flipped classroom model was applied This studyaims to examine the influence of learning outcomes in overall Biology learning, by comparing students in the experimental class and the control class. This study used a quasi-experimental method with a control groupdesign. The research population is all grade VI students at one of the Butung I State Elementary Schools in Makassar. The experimental class was treated with a flipped classroom model, while the control class used a direct learning model. The instrument used in this study is in the form of observation sheets. The results of theanalysis showed that there was a significant influence of communication skills on students who learned withthe flipped classroom model, where their learning outcomes were better than students who learned with thedirect learning model.